2020
DOI: 10.7554/elife.58069
|View full text |Cite
|
Sign up to set email alerts
|

BLOS1 mediates kinesin switch during endosomal recycling of LDL receptor

Abstract: Low-density lipoprotein receptor (LDLR) in hepatocytes plays a key role in plasma clearance of circulating LDL and in whole body cholesterol homeostasis. The trafficking of LDLR is highly regulated in clathrin-dependent endocytosis, endosomal recycling and lysosomal degradation. Current studies focus on its endocytosis and degradation. However, the detailed molecular and cellular mechanisms underlying its endosomal recycling are largely unknown. We found that BLOS1, a shared subunit of BLOC-1 and BORC, is invo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…, 2009 ; Kraehling et al. , 2016 ) and another study that demonstrated a requirement of the BORC subunit BLOS1 for recycling of internalized LDL receptor to the plasma membrane ( Zhang et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2009 ; Kraehling et al. , 2016 ) and another study that demonstrated a requirement of the BORC subunit BLOS1 for recycling of internalized LDL receptor to the plasma membrane ( Zhang et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, as suggested by the large fraction (>50%) of untransfected cells displaying juxtanuclear RAB7 structures, Blos1 regulation may affect eMI in ways unrelated to the simple trafficking and localization of these organelles. In support of this idea, BORC, the BLOS1-containing complex responsible for LE/lysosome trafficking, has also been shown to regulate autophagosome-lysosome fusion 29 and LE/lysosome size 30 ; and BLOS1 itself also participates in a variety of related cellular functions both through its role in the biogenesis of lysosome related organelles complex (BLOC1) and potentially independently 31,32 .…”
Section: Resultsmentioning
confidence: 95%
“…BLOS1 is a member of the BLOC1-related complex (BORC), which links lysosomes to kinesin, allowing for their trafficking toward the periphery of the cell (Pu et al ., 2015). BLOS1 is also important for several other trafficking and endosome-related functions, including the sorting of proteins in endosomal compartments (Zhang et al ., 2014), kinesin switching during endosome recycling (Zhang et al ., 2020), autolysosomal tubulation (Wu et al ., 2021), and tubulin acetylation (Wu et al ., 2018). Degradation of the Blos1 mRNA by RIDD during ER stress leads to the repositioning of LE/ lysosomes to the MTOC and to the enhanced degradation of ubiquitinated proteins (Bae et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a recycling receptor, internalised LDLR could be sorted towards different fates; the regulation between reuse and lysosomal degradation is central to maintaining its protein level. 30 , 31 Based on this, the inhibitors for proprotein convertase subtilisin/kexin 9 (PCSK9) are clinically applied to inhibit the degradation of LDLR in liver and used for cholesterol‐lowering therapies. However, PCSK9 dysfunction mutations are associated with increased circulating fasting glucose concentration, body weight and an increased risk of type 2 diabetes, 32 , 33 suggesting that changes in LDLR levels may trigger unknown metabolic changes for peripheral cells.…”
Section: Discussionmentioning
confidence: 99%